2021
DOI: 10.1007/s13201-021-01447-9
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric analysis of a drainage basin using geographical information system in Gilgel Abay watershed, Lake Tana Basin, upper Blue Nile Basin, Ethiopia

Abstract: GIS and remote sensing approach is an effective tool to determine the morphological characteristics of the basin. Gilgel Abay watershed is stretched between latitude 10.56° to 11.22° N and longitude 36.44° to 37.03° E which is one major contributing river of Lake Tana which is the source of Blue Nile. The present study addressed linear and areal morphometric aspect of the watershed. The study deals with emphasis on the evolution of morphometric parameters such as stream order, stream length, bifurcation ratio,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 7 publications
0
37
0
2
Order By: Relevance
“…GIS&RS is the process-based modelling that play pivotal role in spatial, and dynamic assessment of an area. RS methods have great advantages of synoptic views of wide area, non-destructive, and/or real time base attributes Gao et al [10], Bogale [11].…”
Section: Geospatial Techniquementioning
confidence: 99%
“…GIS&RS is the process-based modelling that play pivotal role in spatial, and dynamic assessment of an area. RS methods have great advantages of synoptic views of wide area, non-destructive, and/or real time base attributes Gao et al [10], Bogale [11].…”
Section: Geospatial Techniquementioning
confidence: 99%
“…The results revealed that the basin is elongated and that the SRTM DEMs have a more significant root mean square error than the CARTOSAT DEMs. The morphometric parameters of Lake Tana and upper Blue Nile basins (Ethiopia) were also assessed using the RS approach and GIS [25]. The results revealed that the study basin, especially Gilgel Abay, is slightly vulnerable to soil erosion and flooding, with a significant contribution of surface runoff on aquifer recharge and groundwater.…”
Section: Introductionmentioning
confidence: 99%
“…An attempt has been undertaken to research the morphometric aspects of the Didessa watershed, which is part of the Blue Nile River basin in Ethiopia's southwestern region [25]. On the Tikur Wuha river watershed, the hydrological aspects of morphometric parameters were evaluated [26,27]. Quantitative morphometry analysis on Ribb and Gumara watersheds has been undertaken to prioritize the watershed for soil and water conservation [28].…”
Section: Introductionmentioning
confidence: 99%